Computed Tomography-Guided Bronchoscopy With an Ultrathin Fiberscope. Issue 4 (1996) - Kobayashi, Toshiaki; Shimamura, Kayako; Hanai, Kohzoh; Kaneko, Masahiro
Abstract : Bronchoscopy was performed under computed tomography (CT) guidance using an ultrathin fiberscope in a patient with a fluoroscopically invisible lesion that was visualized by CT in the rightS 8 and with poor pulmonary function. Under local anesthesia, the ultrathin fiberscope (3 mm in diameter) was inserted close to the lesion (1.5 mm in diameter) under direct visual guidance, and a brush was inserted into the lesion under CT guidance. Cytologic specimens obtained by the brush and washing revealed adenocarcinoma. This is the first report of CT-guided bronchoscopy, which is a new examination method for peripheral small lung lesions and is a less invasive examination than either endoscopic examination with a conventional bronchoscope or open lung biopsy, especially for those with poor pulmonary function.